The associations of decent work with wellbeing and career capabilities: a meta-analysis - Xuebing Su; Ko Ling Chan (Frontiers in Psychology, 2023)
IntroductionAs a global sustainable development goal, the decent work notion has been promoted all over the world at theoretical, practical, and research levels for the purpose of enhancing people's capacity to enjoy freedom, equity, security, and human dignity at work. However, conclusive findings of the impact of decent work on people's wellbeing and longer-term career development are still missing due to a lack of systematic reviews on this topic. This study aims to (a) investigate the associations of decent work with people's wellbeing and their capabilities for sustaining career development and (b) examine the differential associations across different subgroups.MethodsDatabases of literature archived on or before 4 March 2022 were searched. A total of 46 studies met the inclusion criteria and were included in the analysis for the combined Pearson correlation coefficient (r) to estimate the associations of decent work with wellbeing and career capabilities, among which 30 studies (16,026 participants) were used for calculating the association between decent work and wellbeing whereas 26 studies (12,384 participants) were used for decent work and career capabilities.Results and discussionFirst, decent work demonstrates a medium association with wellbeing (r = .48, 95% CI [.45, .51]), and a medium association with career capabilities (r = .44, 95% CI [.40, .49]). Second, no significant differences with respect to the association of decent work with wellbeing and career capabilities were identified across subgroups categorized by developed/developing countries, population type, social status of participants as employee or student, participants from vulnerable/general groups, aspects of wellbeing/career capabilities, and study design. These results pose important implications for informing future research and practice to measure and promote decent work across the world.